1980
DOI: 10.1139/b80-030
|View full text |Cite
|
Sign up to set email alerts
|

Histological and ultrastructural observations of Medicago sativa root nodule senescence after foliage removal

Abstract: Root nodules from control and defoliated alfalfa (Medicago sativa L.) were compared for a period of 18 days following defoliation. Bacteroid containing cells of the nodules decreased markedly for the first 10 days following defoliation, but then increased during the next 8 days. Nodule length increased continuously during the 18 days in both control and defoliated plants. Cellular integrity of vascular bundles, meristems, and infection threads was retained in nodules from treated and control plants throughout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
25
0
1

Year Published

1981
1981
1994
1994

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 0 publications
10
25
0
1
Order By: Relevance
“…The green color of senescing nodules has been reported previously (1,16,21,27). This color is probably due to the destruction of the Lb heme group.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The green color of senescing nodules has been reported previously (1,16,21,27). This color is probably due to the destruction of the Lb heme group.…”
Section: Discussionsupporting
confidence: 76%
“…Senescence of alfalfa nodules can be accelerated as a result of defoliation or prolonged darkness (4,26,27), and the capacity of a single nodule to fix nitrogen can be regained by virtue of reinfection of the meristematic tissue (27 Initial experiments in this laboratory suggested that the metabolic changes observed in soybean nodules as a result of foliar dark treatment, including loss of nitrogenase activity, could be reversed. This study was conducted to investigate the changes in nodular metabolism which occurred as a result of dark-induced senescence, and to document the reversal of this process in soybean nodules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Senescence of alfalfa nodules can be accelerated as a result of defoliation or prolonged darkness (4,26,27), and the capacity of a single nodule to fix nitrogen can be regained by virtue of reinfection of the meristematic tissue (27). The morphology of soybean nodules has been found to be quite different, however.…”
mentioning
confidence: 99%
“…In a greenhouse study, alfalfa was harvested at flowering stage, then regrown for 28 days to 1% flower before being cut again at approximately 3.5-cm stubble height (Vance et al, 1980 …”
Section: Cutting Managementmentioning
confidence: 99%